Sporothrix schenckii sensu lato identification in fragments of skin lesion cultured in NNN medium for differential diagnosis of cutaneous leishmaniasis - Antonio, Liliane de Fátima (2017)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Laboratório de Pesquisa Clínica e Vigilância em Leishmanioses. Rio de Janeiro, RJ, Brasil.